Endo-Perio Lesions: Diagnosis Made Easy - Rashmita Nayak1, Rinkee Mohanty2, Anurag Satapathy1, Abhaya C. Das3, Saurav Panda3, Gatha Mohanty4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
It is not possible to reach into the final diagnosis by only noting the patient history and clinical examination.Appropriate diagnostic aids are mandatory to co-relate the history with the clinical findings to reach into acorrect final diagnosis. It is seen mostly the diagnosis of endo-perio lesion becomes difficult and complicated,unless the clinician possesses sound knowledge regarding the basic diagnostic procedures. Or else, there is afair chance to miss the findings, small though relevant which would lead to an inaccurate diagnosis. Hence,this review topic is taken to help the practitioners with simple basic procedures to make the diagnosis of theendo-perio lesion made easy.